(3JaSjQ YUGes - (3eLghds
(3ChdgG (B:s
(3bhdg CUdg Yf eG aMPa GdCda MPaG cKjQG hSHH GdMPa GdeTGQ Edjg Hbhdg deG eQ jYfj GdSHH Ch bGYOIs
(3BNQgG (B:s
(3dG jNQL HPdc Yf GdJYSa dCf cKQI JcQGQ GdfGS HeYfGg GdhGVM hfSCdg Cf jfJaY Hg Chdj GdCagGe hdG jMQefGs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs